Formic acid, an organic acid food preservative, induces viable-but-non-culturable state, and triggers new Antimicrobial Resistance traits in Acinetobacter baumannii and Klebsiella pneumoniae - Yadav, Manisha; Dhyani, Samridhi; Joshi, Pooja; Awasthi, Sakshi; Tanwar, Subhash; Gupta, Vishal; Rathore, Deepak K.; Chaudhuri, Susmita (Frontiers in Microbiology, 2022)
Numerous human pathogens, especially Gram-negative bacteria, are able to enter the VBNC state when they are exposed to environmental stressors and pose the risk of being resuscitated and causing infection after removal of the trigger. Widely used food preservatives like weak organic acids are potential VBNC inducers in food processing and packaging facilities but have only been reported for food-borne pathogens. In the present study, it is demonstrated for the first time that one such agent, Formic Acid, can induce a VBNC state at food processing, storage and distribution temperatures (4ºC, 25ºC and 37ºC) with varied time of treatment (day 4-10) in pathogenic Gram-negative bacteria Acinetobacter baumanii and Klebsiella pneumoniae. The use of hospital associated pathogens are critical based on earlier reports of presence of these bacteria in hospital kitchens and commonly consumed foods. VBNC induction was validated by multiple parameters e.g., non-culturability, metabolic activity as energy production, respiratory markers and membrane integrity. Further, it was demonstrated that removal of Formic Acid was able to resuscitate VBNC with an increased expression of multiple virulence and AMR genes in both the pathogens. Since food additives/preservatives are significantly used in most food manufacturing facilities supplying to hospitals, contamination of these packaged food with pathogenic bacteria and the consequence of exposure to food additives emerge as pertinent issues for infection control and control of antimicrobial resistance in the hospital setting.